Quality of care for chronic conditions: identifying specificities of quality aims based on scoping review and Delphi survey - Grace Marie V. Ku; Willem van de Put; Deogratias Katsuva; Mohamad Ali Ag Ahmed; Megumi Rosenberg; Bruno Meessen (Global Health Action)
There is a growing need to implement high quality chronic care to address the global burden of chronic conditions. However, to our knowledge, there have been no systematic attempts to define and specify aims for chronic care quality. To address this gap, we conducted a scoping review and Delphi survey to establish and validate comprehensive specifications. The Institute of Medicine’s (IOM) quality of care definition and aims were used as the foundation. We purposively selected articles from the scientific (n=48) and grey literature (n=26). We sought papers that acknowledged and unpacked the plurality of quality in chronic care and proposed or utilised frameworks, studied their implementation, or investigated at least two IOM quality care aims and implementation. Articles were analysed both deductively and inductively. The findings were validated through a Delphi survey involving 49 international chronic care experts with varied knowledge of, and experience in, low-and-middle-income countries. Considering the natural history of chronic conditions and the journey of a person with a chronic condition, we defined and identified the aims of chronic care quality. The six IOM aims apply with specific meanings. We identified a seventh aim, continuity, which relates to the issue of chronicity. The group endorsed our specifications and several participants gave contextualised interpretations and concrete examples. Chronic conditions pose specific challenges underscoring the relevance of tailoring quality of care aims. The next steps require a tailored definition and specific aims to improve, measure and assure the quality of chronic care.